2022
DOI: 10.1021/acsestwater.1c00434
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Trends in COVID-19 Cases and SARS-CoV-2 RNA Wastewater Concentrations in the United States

Abstract: Wastewater-based epidemiology has emerged as a promising technology for population-level surveillance of COVID-19. In this study, we present results of a large nationwide SARS-CoV-2 wastewater monitoring system in the United States. We profile 55 locations with at least six months of sampling from April 2020 to May 2021. These locations represent more than 12 million individuals across 19 states. Samples were collected approximately weekly by wastewater treatment utilities as part of a regular wastewater surve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 38 publications
12
28
0
Order By: Relevance
“…Our finding that normalizing wastewater levels did not substantially alter correlations between wastewater and case data aligned with some previous studies, but not others. In two previous analyses that included data from several sites, findings were similar to our study (16, 21). But in past analyses that largely focused on data from a single site, correlations between wastewater and case data were improved after normalizing wastewater concentrations (22, 23).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our finding that normalizing wastewater levels did not substantially alter correlations between wastewater and case data aligned with some previous studies, but not others. In two previous analyses that included data from several sites, findings were similar to our study (16, 21). But in past analyses that largely focused on data from a single site, correlations between wastewater and case data were improved after normalizing wastewater concentrations (22, 23).…”
Section: Discussionsupporting
confidence: 88%
“…Whereas previous reports from statewide wastewater programs have focused more on urban communities with large WWTPs (16, 21), North Carolina’s statewide program includes rural communities with small WWTPs (the smallest of which serves 3,500 people). The underrepresentation of small WWTPs may explain why Duvallet et al found no relationship between the strength of correlation between PMMoV normalized wastewater and clinical case data and WWTP service population size (21). Our finding that normalizing wastewater levels did not substantially alter correlations between wastewater and case data aligned with some previous studies, but not others.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced strength of the relationship between the PMMoV-population normalized SARS-CoV-2 load and COVID-19 incidence rate was consistent with previous studies that showed PMMoV had mixed or adverse effects on the correlation between wastewater measurements of SARS-CoV-2 and clinical cases. [35][36][37] To the best of our knowledge, there is only one nationwide study to date (conducted by Biobot Analytics) that is comparable with our study in terms of the temporal and spatial magnitudes of sampling. That study collected 2,433 samples from 55 WWTPs across the U.S. and found that PMMoV normalization did not always improve the correlation between wastewater measurement and clinical cases.…”
Section: Paraxanthine Was the Optimal Population Biomarkersupporting
confidence: 66%
“…That study collected 2,433 samples from 55 WWTPs across the U.S. and found that PMMoV normalization did not always improve the correlation between wastewater measurement and clinical cases. 35 Feng et al showed that PMMoV normalizations reduced the correlations between SARS-CoV-2 concentration and COVID-19 incidence for 8 of 12 WWTPs and suggested that variability’s influence across measurement for human viral is stronger than that of differences in the fecal loads in the samples 36 . For some sewersheds where the normalizations by metadata population and without population normalization were better than the normalizations by caffeine and PMMoV estimated population, probably because most WWTPs serve rural areas in Missouri where the population does not fluctuate with time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation